2021
DOI: 10.2166/wcc.2021.018
|View full text |Cite
|
Sign up to set email alerts
|

Performance of potential evapotranspiration models in Peninsular Malaysia

Abstract: Potential evapotranspiration (PET) is an important parameter for the operation of irrigation projects and water resources management. The globally recognized PET estimation model, the FAO-56 Penman–Monteith (FAO-56 PM) model, had been criticized for its requirement of many detailed meteorological variables, but nevertheless has been accepted as the baseline model in many worldwide studies. The performances of different PET models can be found to be excellent for a specific location but may not be representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Various studies have been conducted in various regions of the globe to ascertain the optimised ETo model (Farzanpour et al, 2019;Jing et al, 2019;Khodayvandie et al, 2020;Salam et al, 2020;Goh et al, 2021;Sharafi & Ghaleni, 2021;Trajkovic & Gocic, 2021;Vishwakarma et al, 2022). Tables 3 and 4 In Contrast, the SEE of the modified Hargreavesmethod varied from (0.57) mm per day at Kakul to 22.61 mm per day at Saidu Sharif.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Various studies have been conducted in various regions of the globe to ascertain the optimised ETo model (Farzanpour et al, 2019;Jing et al, 2019;Khodayvandie et al, 2020;Salam et al, 2020;Goh et al, 2021;Sharafi & Ghaleni, 2021;Trajkovic & Gocic, 2021;Vishwakarma et al, 2022). Tables 3 and 4 In Contrast, the SEE of the modified Hargreavesmethod varied from (0.57) mm per day at Kakul to 22.61 mm per day at Saidu Sharif.…”
Section: Overall Discussionmentioning
confidence: 99%
“…The Ma model is a simple radiation-based model for evapotranspiration estimation using temperature and radiation data (Hang et al 2021). The Ma model can be expressed as follows:…”
Section: Ma Modelmentioning
confidence: 99%
“…Priestly and Taylor demonstrated that the net radiation was the main factor influencing the evapotranspiration rate when large areas of land became increasingly saturated, and the P-T model is suitable for humid areas (Hang et al 2021). The P-T model can be expressed as follows:…”
Section: P-t Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Peninsular Malaysia is formed up by eleven states and two federal territories. The total area of Malaysia is 131794 km 2 and is categorized as hot and humid throughout the year [10][11]. In this study, the main focus is on Peninsular Malaysia.…”
Section: Study Areamentioning
confidence: 99%